The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/nhs.12689
|View full text |Cite
|
Sign up to set email alerts
|

Testing general self‐efficacy, perceived competence, resilience, and stress among nursing students: An integrator evaluation

Abstract: The purpose of this study was to develop a predictive model for perceived competence and to obtain an integrator evaluation of the nursing curriculum with measures of nursing self‐efficacy, general self‐efficacy, resilience, and stress among nursing students. A correlational study with nursing students (N = 265) from the degree in nursing was conducted. A factor analysis was used to test the construct validity of nursing self‐efficacy and perceived competence. The correlational and discriminant analyses evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 33 publications
4
15
0
Order By: Relevance
“…Moreover, it was found that higher levels of perceived stress were more often experienced by the students with lower self-esteem and by those with a lower sense of self-efficacy. The studies carried out by other authors have proven that stress has a negative impact on the sense of self-efficacy [ 41 , 42 ]. In addition, the analysis of the results of our own study conducted among students in Poland has revealed that a higher level of perceived stress was associated with lower life satisfaction and a more pessimistic attitude to life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that higher levels of perceived stress were more often experienced by the students with lower self-esteem and by those with a lower sense of self-efficacy. The studies carried out by other authors have proven that stress has a negative impact on the sense of self-efficacy [ 41 , 42 ]. In addition, the analysis of the results of our own study conducted among students in Poland has revealed that a higher level of perceived stress was associated with lower life satisfaction and a more pessimistic attitude to life.…”
Section: Discussionmentioning
confidence: 99%
“…This pandemic can pose a threat to the mental health of the general population (Brooks et al, 2020;Goldschmidt, 2020) but particularly to the parents of adolescents. Adolescence is a time of social, emotional and identity changes that can cause a disturbance in the daily lives of adolescents and their families (Andrews, Foulkes, & Blakemore, 2020;Orkaizagirre-Gómara et al, 2020). Adolescents and their families are particularly vulnerable at this time, their needs being very different from those of children.…”
mentioning
confidence: 99%
“…The aforementioned subcategory confirms that, despite being inherently uncontrollable, individuals who are able to overcome adversity can be transformed or even strengthened in the face of other losses. Although it is useful to study resilience from the point of view of the factors that promote it (Alharbi et al, 2020; Orkaizagirre‐Gómara et al, 2020; Rudzinski et al, 2017), shifting the focus to how and why people become resilient allows for the most subtle forms of adaptation to be captured to guide psychosocial interventions (Rudzinski et al, 2017). By making that shift, we could recognize the pride taken in talking about a new purpose in life (even in the palliative context), the appreciation of the love of family members while receiving their care, and the perception of time like an invaluable loan.…”
Section: Discussionmentioning
confidence: 99%